2007
DOI: 10.1083/jcb.200611106
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane domain organization regulates EGFR signaling in tumor cells

Abstract: Macromolecular complexes exhibit reduced diffusion in biological membranes; however, the physiological consequences of this characteristic of plasma membrane domain organization remain elusive. We report that competition between the galectin lattice and oligomerized caveolin-1 microdomains for epidermal growth factor (EGF) receptor (EGFR) recruitment regulates EGFR signaling in tumor cells. In mammary tumor cells deficient for Golgi β1,6N-acetylglucosaminyltransferase V (Mgat5), a reduction in EGFR binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
262
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(274 citation statements)
references
References 70 publications
10
262
1
1
Order By: Relevance
“…As a consequence, the rate of constitutive endocytosis of the mutant subunit would increase. Interactions of lectins with N-glycans attached to other membrane proteins have been shown to be important for their retention in the plasma membrane in several different cell types (11,47,64,65,68).…”
Section: Role Of N-glycans In Post-golgi Trafficking and Retention Inmentioning
confidence: 99%
“…As a consequence, the rate of constitutive endocytosis of the mutant subunit would increase. Interactions of lectins with N-glycans attached to other membrane proteins have been shown to be important for their retention in the plasma membrane in several different cell types (11,47,64,65,68).…”
Section: Role Of N-glycans In Post-golgi Trafficking and Retention Inmentioning
confidence: 99%
“…These studies showed that Mgat5-dependent recruitment of cytokine receptors (EGFR) to the galectin lattice enhances signaling potential by downregulating receptor endocytosis. 22,23 Further work, including the study described here, demonstrated that Mgat5-dependent recruitment of glycosylated integrins promotes their clustering, decreases local exchange of FA proteins, and favors subsequent FA turnover 8,24 (Fig. 1A).…”
Section: Concerted Regulation Of Focal Adhesion Dynamics By Tyrosinementioning
confidence: 99%
“…Our studies highlight a novel membrane domain, the "Cav1 scaffold", and explain how this non-caveolar Cav1 domain regulates receptor signaling and dynamics. 23 Although the functions of Cav1 outside caveolae remain poorly understood, they are the subject of intensive study. 26,32 For example, Cav1 molecules have been detected in cells lacking caveolae and in non-caveolar regions of cells such as cytoplasm, focal adhesions, the Golgi apparatus, the extracellular milieu, and the nucleus, suggesting potential functions for Cav1 in a variety of cell signaling and mechanotransduction phenomena.…”
Section: Caveolin-1: a Role Beyond Caveolae Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell surface receptors, such as epidermal growth factor receptor (EGFR), is also shown to be associated with the plasma membrane microdomain, where their tyrosine kinases become inactivated (Couet et al, 1997;Waugh et al, 1999;Lajoie et al, 2007). In addition to the signaling cascades involving the secreted extracellular ligands, a class of cell surface resident molecules is also known to be preferentially associated with the membrane microdomain.…”
Section: Two Pathways From the Plasma Membrane To The Endosomesmentioning
confidence: 99%